Efektivitas Penyaluran Zakat, Infaq dan Sedekah untuk Pendidikan (Studi Kasus Zakat Inspirasi Wahdah Sulawesi Tenggara) - Toar, Alfian; Putra, Trisno Wardy; Mongkito, Abdul Wahid; Ramadhan, Sahrul (OIKONOMIKA : Jurnal Kajian Ekonomi dan Keuangan Syariah, 2023)
This research aims to determine the effectiveness and impact of distributing zakat, infaq, and alms (ZIS) funds for educational programs at Wahdah Inspirasi Zakat, Southeast Sulawesi. This research uses descriptive qualitative research with field research methods. The approach used is a case study with data collection methods through observation, interviews, and documentation. From the research results, it was found that the distribution of ZIS funds to the education program at Wahdah Inspirasi Zakat, Southeast Sulawesi has not been effective, because the Zakat funds collected from 2020 to 2022 have not been distributed as a priority to the education program. However, Wahdah Inspiration Zakat Sultra has distributed these funds for routine education every year in a scholarship program. Apart from that, the zakat, infaq, and alms (ZIS) distribution program at Wahdah Inspirasi Zakat Southeast Sulawesi has had a positive impact on zakat, infaq, and alms (ZIS) mustahik, including students with assistance with education costs.